Gender Negotiation, Religious Identity, and Social Identity among Female Pilgrims (Ebhu Ajjhi) in Rural Madura - Hidayat, Medhy Aginta; Afifuddin, Mohammad (IAIN Palangka Raya, 2024)
Madurese society gives privileges and high social status to those who have the title of Hajj. However, research on the Hajj in Madura focused more on the perspective of male Hajj (Ajjhi). In fact, the number of female pilgrims in Madura is higher than the number of males. The research aimed to explain the process of forming gender identity, religious identity, and social identity of Hajj from the perspective of female Hajj (Ebhu Ajjhi) in Madura. The research used qualitative methods, with a phenomenological approach. Data was obtained from observations and in-depth interviews with 16 informants in Bangkalan and Sampang, Madura. Data was analyzed using the Denzin model with a theoretical framework of identity construction, social capital, and symbolic capital. It found that the Hajj title influenced changes in Ebhu Ajjhi's physical and non-physical identity. Physical changes include more conservative clothing, meanwhile non-physical changes include increasing socio-economic-cultural access. Hajj title are also a source of social capital and symbolic capital, growing new networks, building trust and respect. However, the privilege of the title of Hajj in Madura is mainly enjoyed by male Hajj. Traditional gender roles shape different perceptions about Hajj title in Madura. Even though he has the title of Hajj, Ebhu Ajjhi's role are limited to the domestic sphere.